Utilization of Local Wisdom “Anglo” as an Effort to Increase the Competitiveness of Fried Rice Business - Cintyawati, Anggita Putri Puspita Dwi; Subagyo (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : Analyzing the utilization of local wisdom anglo as a strategy to improve the competitiveness of fried rice businesses, through a product differentiation.Design/Methode/Approach : This research uses descriptive qualitative methods with data collection techniques through in-depth interviews. Informants were selected purposively based on the 5R criteria.Research Finding : Based on the results of the research, it was found that the utilization of the Anglo as an effort to increase competitiveness can be seen from its distinctive characteristics derived from clay, theunique taste produced, and the attractiveness it offers to consumers.Theoretical contribution/Originality : This research adds insight into the importance of local wisdom integration in culinary business development, especially in popular products such as fried rice, which has not been widely explored from the perspective of local culture and marketing strategies.Practitionel/Policy implication : This research can provide practical insights for culinary business owners, especially fried rice businesses, to understand the importance of local distinctiveness in improving thecompetitiveness of their products. This research can also provide practical benefits for other researchers by providing insight into how local distinctiveness can be utilized as a differentiation strategy in improving the competitiveness of culinary products Research limitation : This research is limited to the Kediri City area and uses a small number of respondents, The research also has not explored the potential for business collaboration or changes in consumer trends at large.